Pengaruh Perubahan Iklim Terhadap Cekaman Kekeringan pada Tanaman Perkebunan di Pulau Ternate - Amiruddin, Amiruddin; Umasugi, Buhari (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2023)
This research aims to determine the type and number of plantation crops experiencing drought and determine the environmental factors that influence the drought of plantation crops on Ternate Island. This research uses survey methods and direct observation in the field. Inventory of drought in plantation crops by making 16 sample plots measuring 100 x 100 m, representing the North, East, South and West slopes. Data analysis using tabulation, statistical and descriptive methods. Determination of drought uses criteria for the level of drought in plantation crops which is based on morphological factors and plant production. The results of the research showed that the total number of plantation plants in the dry category was 1,117 plants (40%), slightly dry, 604 plants (21.6%) and not dry, 1,070 plants (38.3%). The composition of plantation plant types in the dry category includes 886 clove plants, 199 nutmeg plants and 32 coconut plants. The Slightly Dry category includes 427 clove plants, 110 nutmeg plants and 67 coconut plants. Meanwhile, the composition of non-dry plants includes 434 clove plants, 341 nutmeg plants and 295 coconut plants.